Cinematografias afrodiaspóricas: imagens e narrativas sob regimes de oralidade - Braga, Liliane Pereira (2018)
The use of cinematographic sources from Haiti, Cuba, Jamaica and Brazil in this research intends to escape the “archival power”, accompanying Michel-Rolph Trouillot (1995) and his questioning, in ways of deconstructing universal metanarratives and de-silencing of History. Challenging images and sounds of the 21st century aims to approach the traditions and ways of life of Afro-Latin American groups. Tracks opened by dimensions of postcolonial studies and cultural studies served as a starting point against the power of discourse, analyzing practices of representation that impose a “regime of truth” and mark cultural difference by signifying "the racialized 'Other' in Western popular culture" (HALL, 2016). While searching for what emerges when the „Other‟ represents his/herself from their own positionality and epistemic perspectives of the South, this work intentionally draws on references that produce knowledge and theories „otherwise‟, decentering Global North‟s instrumental rationalism. Approaching socialized cultures ruled by "regimes of orality" (ANTONACCI, 2016) requires getting close to multifaceted ways of being, living and knowing manifested in cognitive and communicational practices. It requires apprehending distinctions, and considering that the unforeseen of encounters / confrontations in the so-called New World have resulted in a plurality of Afrodiasporic cultures. As paradigms are being redefined, "musicosmoving afroepistemes" are being surveyed, confronting the concept of literacy and its lack of consideration for the senses. The term coined in this research pluralizes epistemes from a sensory-corporeal-reason standpoint, where the rhythm allows for alignment with the time of the Cosmos, updating and actualizing ideas that do not constitute themselves individually, but as a whole, as performances – “vital acts of transfers" (TAYLOR, 2013) – as seen in cinematographies I have used in this work